Impact of combiner aerobic and resistance training on depression: a systematic review and meta-analysis of randomized controlled trials - Hai Wang; Qinzheng Liu; Yingxu Pan (BMC Sports Science, Medicine and Rehabilitation)
Abstract Objective To summarize the existing literature and evaluate the efficacy of combined resistance and aerobic training in alleviating depressive symptoms among individuals with depression. Subgroup analyses were conducted based on study region, age, depression severity, intervention duration, intervention frequency, and whether the intervention was supervised or unsupervised. Methods Five databases were thoroughly examined from database establishment until August 20, 2024, to find randomized controlled trials that investigated resistance combined aerobic training impact on depression. Results Finally, 27 eligible studies were included, involving a total of 2,342 patients with depression. The outcomes indicated that resistance combined aerobic training notably improved signs of depression in these patients (SMD=-1.39, 95%CI=-1.80 to -0.96, p = 0.000). Subgroup analysis based on study area, age, severity of depressive symptoms, and exercise prescription revealed that resistance combined aerobic training had a particularly significant effect on middle-aged and elderly patients with depression, as well as on those with moderate depression. Additionally, moderate period (9–24 weeks), moderate frequency (3–4 times per week), a total weekly duration of more than 180 min and supervised training displayed the best results. Conclusion Resistance combined aerobic training serves as an efficient approach to relieve depression-related symptoms, particularly in middle-aged and elderly patients with depression and those with moderate depression. Moderate training intensity, duration, frequency, and total weekly duration offer the greatest benefit.